2013
DOI: 10.6004/jnccn.2013.0021
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab in the Treatment of CD30-Positive Enteropathy-Associated T-Cell Lymphoma

Abstract: Enteropathy-associated T-cell lymphoma (EATL) is a rare aggressive lymphoma that confers a poor prognosis with current treatment strategies. Given the rarity of this disease, prospective randomized trials are limited, and thus a standard validated treatment strategy is lacking. This report presents the disease course of a patient with EATL who was treated with single-agent brentuximab vedotin, an anti-CD30 conjugated antibody. (JNCCN 2013;11:137-140) NCCN: Continuing Education Accreditation StatementThis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The neoplastic cells are usually cCD3 + , CD5 − , CD4 − , CD8 − and CD56 − , and diffusely express cytotoxic markers with an activated profile (TIA1, granzyme B and/or perforin) . Most cases are CD30 + and interestingly, complete remission was reported recently in a patient with CD30 + EATL after brentuximab vedotin administration . The neoplastic cells are EBV‐negative, and usually express T‐cell receptors (TCR)‐αβ and the intraepithelial homing integrin CD103 …”
Section: Lymphomas and Indolent Lymphoproliferations Of Natural Killementioning
confidence: 98%
“…The neoplastic cells are usually cCD3 + , CD5 − , CD4 − , CD8 − and CD56 − , and diffusely express cytotoxic markers with an activated profile (TIA1, granzyme B and/or perforin) . Most cases are CD30 + and interestingly, complete remission was reported recently in a patient with CD30 + EATL after brentuximab vedotin administration . The neoplastic cells are EBV‐negative, and usually express T‐cell receptors (TCR)‐αβ and the intraepithelial homing integrin CD103 …”
Section: Lymphomas and Indolent Lymphoproliferations Of Natural Killementioning
confidence: 98%
“…Studies of allogenic stem cell transplant in relapsed and refractory aggressive non-Hodgkin lymphoma suggest that it could have a role in treatment, although it is unclear whether this could be extrapolated to EATL 20 21. Some authors have also suggested that newer therapies such as monoclonal antibodies and apoptosis inducing small molecules may be used to treat EATL in the future, and there has been success in individual cases 12 22. There appears to be a very limited role for surgery and radiotherapy, to be used for debulking and resection of masses with high risk of obstruction, based on clinical judgement 2.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I study comparing the safety of brentuximab vedotin combined to either ABVD or AVD chemotherapy found a high number of pulmonary toxicity in the ABVD arm [54]. Brentuximab vedotin has also shown clinical efficacy in anaplastic large cell lymphoma and case reports indicate efficacy in other CD30þ aggressive lymphomas such as enteropathy type T-cell lymphoma and preclinical evidence suggests a potential role in the treatment of primary effusion lymphoma [55][56][57].…”
Section: Hodgkin Lymphomamentioning
confidence: 96%